2012
DOI: 10.5194/bg-9-2111-2012
|View full text |Cite
|
Sign up to set email alerts
|

Towards a merged satellite and in situ fluorescence ocean chlorophyll product

Abstract: Abstract. Understanding the ocean carbon cycle requires a precise assessment of phytoplankton biomass in the oceans. In terms of numbers of observations, satellite data represent the largest available data set. However, as they are limited to surface waters, they have to be merged with in situ observations. Amongst the in situ data, fluorescence profiles constitute the greatest data set available, because fluorometers have operated routinely on oceanographic cruises since the 1970s. Nevertheless, fluorescence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 55 publications
4
55
0
Order By: Relevance
“…However, this calibration method based on the existence of simultaneous in situ samples is not always applicable. Alternative calibration methods, independent of concomitant HPLC observations, have therefore recently been developed (Boss et al, 2008;Xing et al, 2011;Lavigne et al, 2012). They are based on additional information such as irradiance profiles , ocean color observations (Boss et al, 2008;Lavigne et al, 2012) or the shape of the fluorescence profile .…”
Section: H Lavigne Et Al: On the Vertical Distribution Of The Chlormentioning
confidence: 99%
See 1 more Smart Citation
“…However, this calibration method based on the existence of simultaneous in situ samples is not always applicable. Alternative calibration methods, independent of concomitant HPLC observations, have therefore recently been developed (Boss et al, 2008;Xing et al, 2011;Lavigne et al, 2012). They are based on additional information such as irradiance profiles , ocean color observations (Boss et al, 2008;Lavigne et al, 2012) or the shape of the fluorescence profile .…”
Section: H Lavigne Et Al: On the Vertical Distribution Of The Chlormentioning
confidence: 99%
“…Alternative calibration methods, independent of concomitant HPLC observations, have therefore recently been developed (Boss et al, 2008;Xing et al, 2011;Lavigne et al, 2012). They are based on additional information such as irradiance profiles , ocean color observations (Boss et al, 2008;Lavigne et al, 2012) or the shape of the fluorescence profile . Although these new calibration methods do not reach the accuracy of HPLC-based calibration, they offer an acceptable alternative to extract reliable estimates of [Chl a] vertical profiles from a large quantity of fluorescence profiles.…”
Section: H Lavigne Et Al: On the Vertical Distribution Of The Chlormentioning
confidence: 99%
“…For this specific purpose, FLUO profiles were smoothed, using a 5-point moving median filter, and the MLD was calculated from density profiles, using a 0.03 kg m −3 density criterion (de Boyer Montegut et al, 2004). The relevance of this NPQ correction in oligotrophic areas was specifically addressed in Lavigne et al (2012), which showed it has a positive and significant impact on the estimates of chlorophyll.…”
Section: Fluorescence Profiles Calibrationmentioning
confidence: 99%
“…Although this method was not directly validated in the GOM, a comparison between satellite-calibrated profiles and in situ HPLC [CHL] data was performed by Lavigne et al (2012) at the station BATS (32 • N and 64 • W, in the Sargasso Sea). It was shown that calibrated profiles were unbiased with an associated median error of 29 %, which is reduced to 16 % when climatological averages are compared.…”
Section: Fluorescence Profiles Calibrationmentioning
confidence: 99%
See 1 more Smart Citation